Utility Maximization in Nonconvex Wireless Systems - Brehmer, Johannes; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This monograph formulates a framework for modeling and solving utility maximization problems in nonconvex wireless systems. First, a model for utility optimization in wireless systems is defined. The model is general enough to encompass a wide array of system configurations and performance objectives. Based on the general model, a set of methods for solving utility maximization problems is developed. The development is based on a careful examination of the properties that are required for the application of each method. The focus is on problems whose initial formulation does not allow for a solution by standard convex methods. Solution approaches that take into account the nonconvexities inherent to wireless systems are discussed in detail. The monograph concludes with two case studies that demonstrate the application of the proposed framework to utility maximization in multi-antenna broadcast channels.
General Problem Setup -- Solution Methods -- Physical Layer Models -- Utility Models -- Case Studies.
Keywords: Engineering; Computer science; Mathematics; Telecommunication; Engineering; Communications Engineering, Networks; Models and Principles; Information and Communication, Circuits